Chitosan/Gold Hybrid Nanoparticles Enriched Electrospun PVA Nanofibrous Mats for the Topical Delivery of Punica granatum L. Extract: Synthesis, Characterization, Biocompatibility and Antibacterial Properties - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2021)
Purpose: Intending to obtain Punica granatum L. extract (PE)-loaded drug delivery system of better impact and biomedical applicability, the current study reports the use of crosslinked PVA nanofibers (NFs) as platforms incorporating different amounts of biosynthesized PE-CS-gold nanoparticles (PE-CS-Au NPs). Methods: PE-conjugated CS-Au nanoparticles (PE-CS-Au NPs) were synthesized via green chemistry approach. The formation of PE-CS-Au NPs was confirmed by UV spectroscopy, DLS, SEM and STEM. PE-CS-Au NPs were then dispersed into polyvinyl alcohol (PVA) solution at different ratios, where the optimized ratios were selected for electrospinning and further studies. Crosslinking of PE-CS-Au NPs loaded PVA nanofibers (NFs) was performed via glutaraldehyde vapor. The morphology, chemical compositions, thermal stability and mechanical properties of PE-CS-Au NPs loaded NFs were evaluated by SEM, FTIR and DSC. Swelling capacity, biodegradability, PE release profiles, release kinetics, antibacterial and cell biocompatibility were also demonstrated. Results: By incorporating PE-CS-Au NPs at 0.6% and 0.9%, the diameters of the nanofibers decreased from 295.7 +/- 83.1 nm in neat PVA to 165.6 +/- 43.4 and 147.8 +/- 42.7 nm, respectively. It is worth noting that crosslinking and incorporation of PE-CS-Au NPs improved thermal stability and mechanical properties of the obtained NFs. The release of PE from NFs was controlled by a Fickian diffusion mechanism (n value <0.5), whereas Higuchi was the mathematical model which could describe this release. The antibacterial activity was found to be directly proportional to the amount of the incorporated PE-CS-Au NPs. The human fibroblasts (HFF-1) showed the highest viability (123%) by seeding over the PVA NFs mats containing 0 9% PE-CS-Au NPs. Conclusion: The obtained results suggest that the electrospun PVA NFs composites containing 0.9% PE-CS-Au NPs can be used as antibacterial agents against antibiotic-resistant bacteria, and as suitable scaffolds for cell adhesion, growth and proliferation of fibroblast populations.
Keywords: gold nanoparticles; chitosan; Punica granatum; nanofiber; antibacterial; POLYVINYL-ALCOHOL; POLY(METHYL METHACRYLATE); GOLD NANOPARTICLES; WOUND DRESSINGS; POMEGRANATE; COMPOSITE; DIFFERENTIATION; COMPATIBILITY; PERFORMANCE; VISCOSITY